Experimental Inoculation in Rats and Mice by the Giant Marseillevirus Leads to Long-Term Detection of Virus - Aherfi, Sarah; Nappez, Claude; Lepidi, Hubert; Bedotto, Marielle; Barassi, Lina; Jardot, Priscilla; Colson, Philippe; La Scola, Bernard; Raoult, Didier; Bregeon, Fabienne (Frontiers in Microbiology, 2018)
The presence of the giant virus of amoeba Marseillevirus has been identified at many different sites on the human body, including in the bloodstream of asymptomatic subjects, in the lymph nodes of a child with adenitis, in one adult with Hodgkin’s disease, and in the pharynx of an adult. A high seroprevalence of the Marseillevirus has been recorded in the general population. Whether Marseillevirus can disseminate and persist within a mammal after entry remains unproven. We aimed to assess the ability of the virus to disseminate and persist into healthy organisms, especially in the lymphoid organs. Parenteral inoculations were performed by intraperitoneal injection (in rats and mice) or intravenous injection (in rats). Airway inoculation was performed by aerosolization (in mice). Dissemination and persistence were assessed by using PCR and amebal co-culture. Serologies were performed by immunofluorescent assay. Pathological examination was conducted after standard and immunohistochemistry staining. After intraperitoneal inoculation in mice and rats, Marseillevirus was detected in the bloodstream during the first 24 hours. Persistence was noted until the end of the experiment, i.e., at 14 days in rats. After intravenous inoculation in rats, the virus was first detected in the blood until 48 hours and then in deep organs with infectious virus detected until 14 and 21 days in the liver and the spleen, respectively. Its DNA was detected for up to 30 days in the liver and the spleen. After aerosolization in mice, infectious Marseillevirus was present in the lungs and nasal associated lymphoid tissue until 30 days post inoculation but less frequently and at a lower viral load in the lung than in the nasal associated lymphoid tissue. No other site of dissemination was found after aerosol exposure. Despite no evidence of disease being observed, the 30-day long persistence of Marseillevirus in rats and mice, regardless of the route of inoculation, supports the hypothesis of an infective potential of the virus in certain conditions. Its constant and long-term detection in nasal associated lymphoid tissue in mice after an aerosol exposure suggests the involvement of naso-pharyngeal associated lymphoid tissues in protecting the host against environmental Marseillevirus.